The TeX Live guide, 4th edition - Rahtz, S; Goossens, M (TeX Users' Group, 1999)
This documentation describes the main features of the TeX Live 4 CD-ROM---a TeX/LaTeX distribution for Unix and Windows32 systems that includes TeX, LaTeX2e, Metafont, MetaPost, Makeindex, and BibTeX; and a wide-ranging set of macros, fonts and documentation conforming to the TeX Directory Standard (TDS)---which can be used with nearly every TeX setup. This TeX package uses the Web2c (version 7.3) implementation of the programs, which tries to make TeXing as easy as possible, and takes full advantage of the efficient and highly customizable Kpathsea library from Karl Berry and Olaf Weber. It can be run either directly from the CD-ROM or installed on a hard disk. Most of the runnable systems on the CD-ROM include a large set of drivers and support programs for TeX, including dvips (PostScript driver), xdvi (X Windows previewer), dvilj (HP LaserJet driver), lacheck (LaTeX syntax checker), tex4ht (TeX to HTML converter), dviconcat and dviselect, dv2dt and dt2dv (dvi to ASCII and vice versa), and Angus Duggan's PostScript utilities.